2020
DOI: 10.1186/s40945-020-00089-5
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and outcomes of an individualized exergaming telePT program for veterans with multiple sclerosis: a pilot study

Abstract: Background Physical rehabilitation services are an important component of treatment for persons with multiple sclerosis (PwMS) to improve and maintain physical mobility. However, PwMS often have significant barriers to outpatient physical therapy (PT) services including mobility deficits and lack of transportation. The integration of exercise gaming (exergaming) and telehealth into clinical PT practices may overcome these barriers. The overarching purpose of this pilot study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 53 publications
4
49
0
Order By: Relevance
“…123 A recent study with 10 participants with MS showed satisfactory results in balance and gait, but not for fatigue, after a telerehabilitation intervention based on Nintendo Wii exergames. 124 With regard to our protocol, because Oculus Quest is wireless and portable, exercises can be performed at the laboratory, in public, in private clinics and at home. In addition, this HMD has two features to ensure safety.…”
Section: Clinical Applicability Of Vri Vestibular Rehabilitationmentioning
confidence: 99%
“…123 A recent study with 10 participants with MS showed satisfactory results in balance and gait, but not for fatigue, after a telerehabilitation intervention based on Nintendo Wii exergames. 124 With regard to our protocol, because Oculus Quest is wireless and portable, exercises can be performed at the laboratory, in public, in private clinics and at home. In addition, this HMD has two features to ensure safety.…”
Section: Clinical Applicability Of Vri Vestibular Rehabilitationmentioning
confidence: 99%
“…Six studies were randomised controlled trials, 50,51,56,60,63,67 four were two-group prospective non-randomised controlled trials, 55,57,61,66 and seven were single-group pre-post designs. 45,52,58,59,62,64,65 Stroke was the focus in nine studies, 45,50,56,57,59,61,62,64,67 multiple sclerosis in four 55,58,60,63 and Parkinson's disease in three. 51,52,66 One study included a mix of conditions (i.e., multiple sclerosis, Parkinson's disease and supranuclear palsy).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst several studies conducted an initial assessment and/or training in-person, 50,52,58,59,62,63 all utilised synchronous videoconferencing to deliver interventions with clinicians based remotely. Four studies were not based in participants’ homes, instead using telehealth at community centres, 61,64,66 or a simulated home environment situated in a hospital outpatient room.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence showing benefits of telerehabilitation specially in patients after stroke [34][35][36] , but also in other neurological conditions, such as Parkinson disease 37 , vestibular disorders 38 and multiple sclerosis 39 . Telerehabilitation is characterized not only by video contact between patient and physical therapist, but can include virtual reality and applications for self-managed exercises 36,38 , without therapist guidance.…”
Section: Discussionmentioning
confidence: 99%